Studi Kelayakan Pengembangan Bisnis pada PT Dagang Jaya Jakarta - Santi Nurjanah (The Winners, 2013)
The purpose of the study is to determine the feasibility of the development of the business conducted by PT Dagang Jaya. Research method used is based on the analysis of aspects of business feasibility study, the aspects of Finance, Markets and Marketing, Management and HR, Legal aspects, Engineering and Operations, EIA, and the Economic and Social aspects. The results of the analysis of each aspect showed positive results stating that the Business Development conducted by PT Dagang Jaya feasible to run. Conclusions from this research is the development of the business conducted by PT Dagang Jaya feasible to run one way to choose business development is to increase the number and variety of products distributed by the company.